Evaluating the effectiveness of virtual reality-based rehabilitation programs for post-injury recovery in adolescent athletes: a mixed-methods study - V Kiran MPT; R. Amarnath; G Nusarath jaha; Praveen Katiyar; Rashmi Rangaswamy; Avanika Sinha (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: the importance of post-injury rehabilitation for teenage athletes demands innovative methods because traditional practices fail to sustain student athlete participation. VR-based rehabilitation creates interactive recovery programs which might advance physical healing together with mental drive.